Three-Dimensional Representations of Children's Songs and Its Implementation in Character Education - Widayati, Mukti; Nugrahani, Farida; Sudiyana, Benedictus; Iriani SRT , Rina (Devotion : Journal of Research and Community Service, 2024)
This research aims to describe the aesthetic pattern and meaning of songs children created by Indonesian authors from the 60s to 70s. The songs it is very familiar and frequently sung by children of their time. The spread of children's songs at that time only through radio and electronic television media, which was still very rare and owned by the people of Indonesia at that time. In this digital age, the spread of children's songs conducted through digital media is very fast, good in audio and audio-visual form. The development of technology makes it convenient for children to recognise songs. The second aim is to describe the meaning of character education in three dimensions: the connection between man with God, man with humans, and humans with nature. This study use theory focused on eco-strategy analysis problem environment existing life in literary works. Next, the meaning of three dimensions could be implemented in character education for students in kindergarten and elementary schools.